Migration, Security and Resilience : Women Migrants in Kota Kinabalu, Sabah, East Malaysia - Sulehan, Junaenah; Ramli, Rashila; Idris, Nor Azizan (Philippine Journal of Labor and Industrial Relations, 2020)
Migration is an old issue in development, a manifestation of people’s mobility as a response to socio-economic and physical changes around them, with the ultimate objective of enhancing the migrants’ quality of life. However, this phenomenon is worth examining especially in this age of globalisation which encourages and accentuates human mobility for several reasons. The impact and implication of migration demand a multi-dimensional approach analysis and comprehension. This paper has three objectives. First, it highlights the in􀏔lux of foreign workers to Sabah, East Malaysia which is discussed within the historical context of why this phenomenon is a never-ending issue. Second, this paper focuses on security issues and gender in relation to the presence of increasing number of immigrants, and in particular, how these issues affect female immigrants. Third, this paper discusses survival issues among women immigrants working in various sectors in urban centers — how they culturally adapt, live, sustain and face security aspects in the country of destination. For decades, even before the formation of the Federation of Malaysia, Kota Kinabalu had been the ‘economic magnet’ to foreign immigrants, in particular from the Philippines and Indonesia. Security is one of the compelling issues, notably, how the presence of immigrants have an impact on the city’s public and human security. The increasing apprehension and discrimination towards foreign immigrants requires the need to understand security at the state/national level, the community level and the individual level. This paper seeks to understand how factors such as the process of adaptation, cultural resilience and local resentment affect women immigrants. This paper also illustrates how the state government, in dealing with security issues, intervened stringently in countering immigrant-related problems in order to make Kota Kinabalu a safe city.